Comparison of power-ecological characteristics of diesel engine work on mixed diesel fuels on the basis of ethyl esters of rapeseed and sunflower oils - Patrylak, Lyubov; Patrylak, Kazymyr; Okhrimenko, Mykhailo; Zubenko, Stepan; Levterov, Anton; Savytskyi, Volodymyr (Publishing House of Lviv Polytechnic National University, 2015)
Power-ecological characteristics of diesel engine work on ethyl esters of rapeseed and sunflower oils and their blends with mineral diesel have been studied. Acceptable power and high environmental performance of the engine work on the studied fuels have been established. It is shown that fuels on the basis of sunflower oil are slightly inferior to fuel on the basis of rapeseed oil in energy performance but surpasses them in environmental performance. Оцінено енергоекологічні характеристики роботи тракторного дизельного двигуна на етилових естерах ріпакової та соняшникової олій, а також на їх сумішах з мінеральним дизельним паливом. Встановлено прийнятні енергетичні та високі екологічні показники роботи двигуна на досліджуваних паливах. Показано, що палива на основі соняшникової олії дещо поступаються паливам на основі ріпакової олії за енергетичними показниками, але переважають їх за екологічними.
Порівняння потужнісно-екологічних характеристик роботи дизельного двигуна на сумішевих паливах на основі етилових естерів ріпакової та соняшникової олій
Keywords: transesterification; ethanol; fatty acid ethyl esters; power characteristics; ecological performancе; переестерифікація; спирт етиловий; жирних кислот етилові естери; характеристики потужнісні; показники екологічні